2020
DOI: 10.1038/s41540-020-00153-7
|View full text |Cite
|
Sign up to set email alerts
|

Model-driven design allows growth of Mycoplasma pneumoniae on serum-free media

Abstract: Mycoplasma pneumoniae is a slow-growing, human pathogen that causes atypical pneumonia. Because it lacks a cell wall, many antibiotics are ineffective. Due to its reduced genome and dearth of many biosynthetic pathways, this fastidious bacterium depends on rich, undefined medium for growth, which makes large-scale cultivation challenging and expensive. To understand factors limiting growth, we developed a genome-scale, constraint-based model of M. pneumoniae called iEG158_mpn to describe the metabolic potentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 69 publications
3
31
0
Order By: Relevance
“…This gene was classified as non-essential at least in one of the essentiality studies in M. pneumoniae 82 . This was confirmed simulating in silico the disruption of each gene comprised in the most updated metabolic model of M. pneumoniae (iEG158_mpn) 83 , which showed that the disruption of mpn062 would decrease growth only 1.2% (Suppl. Table 4).…”
Section: IIIsupporting
confidence: 59%
See 1 more Smart Citation
“…This gene was classified as non-essential at least in one of the essentiality studies in M. pneumoniae 82 . This was confirmed simulating in silico the disruption of each gene comprised in the most updated metabolic model of M. pneumoniae (iEG158_mpn) 83 , which showed that the disruption of mpn062 would decrease growth only 1.2% (Suppl. Table 4).…”
Section: IIIsupporting
confidence: 59%
“…The most updated metabolic model of M. pneumoniae (iEG158_mpn) 83 comprises all genes involved in the metabolism of this microorganism that have been annotated. Each gene included in the model has been disrupted in silico by allowing no flux through the reactions linked to the specific gene.…”
Section: Simulation Of Gene Disruption In M Pneumoniae Through Metabolic Modellingmentioning
confidence: 99%
“…Most of the driver reactions are not associated with annotated genes, as many transporter proteins are putative-however, given that M. genitalium synthesises very few compounds and gains most from its surrounding media, this is an important knowledge gap. The external media for Mycoplasma culture is generally undefined rich media, so knowledge of exactly which of the media components are essential for growth would be valuable for lab use and simplify Mycoplasma production (Gaspari et al, 2020). This may also help with linking unannotated genes with modelled functions, leading to better understanding of the M. genitalium genome.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is proven that mg517 and mpn483 share 77% of gene sequence similarity, the enzymatic activities slightly differ in terms of specificity (Andr es, 2011). The essentiality of mpn483, not excluded by gene transposon analysis (Lluch-senar et al, 2015), is expected as M. pneumoniae uses this enzyme to perform synthesis of many other lipids in the membrane (Klement, 2007), which we know are crucial for its survival (Gaspari et al, 2020). In the same way, the gene transposon analysis conducted by Lluch-Senar et al suggests mpn075 and mpn257, respectively, coding for the glycosyltransferase MPN_075 and the epimerase MPN_257, might be essential, at the contrary of mpn028, coding for the third glycosyltransferase, which is reported to be non-essential.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an experimental application of our computational results would represent a suitable approach to render this bacterium safe in its numerous applications. In fact, other attempts to avoid biosynthesis of galactocerebroside seem to be not trivial: it would not be possible to knock-out genes involved in sphingolipid transporter since this transporter would not only import ceramide but also very important lipids such as sphingomyelin that were shown to be essential to the survival of M. pneumoniae (Gaspari et al, 2020). Instead, the introduction of a ceramidase, disassembling ceramide into its sphingosine backbone and fatty acids chains, is another potential strategy to integrate.…”
Section: Discussionmentioning
confidence: 99%